Microbiological pollutants in air and antibiotic resistance profile of some bacterial isolates - Kabir, Md Shahinur; Mridha, Farzana; Islam, Salma; Shorifujjaman, Md (Jahangirnagar University Journal of Biological Sciences, 2016)
Microbiological quality assessment is one of the most important investigations to determine the pollution of indoor and outdoor air. To evaluate the microbial load in air, samples were collected from 3 different outdoor and 3 different indoor sites within Jahangirnagar University campus. In outdoor air, bacterial and fungal counts varied from 117 - 7284 CFU/m3 and 88 - 5287 CFU/m3, respectively. On the other hand, in indoor air bacterial and fungal counts varied from 440 - 6226 CFU/m3 and 88 - 5874 CFU/m3, respectively. Furthermore, to reveal the antibiotic resistance profile, Staphylococcus aureus isolates were subjected to antibiogram study against 14 antibiotics. Among the isolates, 87.5% exhibited resistance to ceftazidime; 50% to penicillin G; 31.25 % to cefotaxime; 25 % to ceftriaxone, cefuroxime, cloxacillin; and 18.75% to amoxicillin. None of the isolates showed resistance to amikacin, ciprofloxacin, erythromycin, gentamicin, imipenem, nitrofurantoin and vancomycin. The presence of antibiotic-resistant bacteria in air may cause serious health hazard to the people living in this area. Jahangirnagar University J. Biol. Sci. 5(1): 47-56, 2016 (June)